The Effect of Intravenous vitamin C on Ferritin Levels in Patients Hemodialysis Patients, A Clinical Trial (Iranian Journal of Kidney Diseases, 2022)
Introduction. Administration of intravenous vitamin C in hemodialysis patients can reduce their ferritin levels. Nevertheless, little research has been carried out in this regard. Hence, this study aimed to determine the effect of intravenous vitamin C on ferritin levels in a group of hemodialysis patients. Methods. The study population included 32 patients with chronic renal failure undergoing hemodialysis who had been referred to Qazvin Hospital. These patients had functional iron deficiency (IDA) and high levels of serum ferritin. Patients were randomly allocated into intervention group A (n = 16) and control group B (n = 16). Group A was given intravenous ascorbic acid, while group B was given the same amount of distilled water as a placebo three times a week after each dialysis session for three months along with erythropoietin. Laboratory parameters were assessed at the beginning and the end in an interval of three months. Results. In patients who received vitamin C injections, the mean ferritin level decreased at the end of the study (P < .05). But vitamin C intake did not affect BUN, creatinine, sodium, potassium, TIBC, hemoglobin, platelets count, and the length and number of dialysis sessions. Conclusion. Results of our study showed that vitamin C can reduce serum ferritin levels in hemodialysis patients. Therefore, it can be used as an adjunct in the treatment of anemia in patients.  DOI: 10.52547/ijkd.6531